Penggunaan Pendekatan CTL (Contextual Teaching And Learning) Dalam Meningkatkan Hasil Belajar Matematika Dalam Materi Aljabar Pada Siswa Kelas VIIB Di MTs Negeri 1 Kota Surabaya - Wilujeng, Dita Wahyu; Prastiwi, Lusiana; Huda, Nuril (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2017)
The result of study of student of class VII B in MTs Negeri 1 Kota Surabaya on the subject of wake up flat in academic year 2017/2018 after analyzed have low result, this is allegedly because approach of learning at that time not yet right, hence in this class research used approach of learning Contex Teaching and Learning (CTL), which emphasizes the concept of learning that helps teachers connect between the material they teach and the students' real-world situations and encourages students to make connections between their knowledge and application in daily life. The problem to be discussed is whether the learning of mathematics with CTL approach on the subject of wake up flat can improve student learning outcomes of class VII B in MTs Negeri 1 Kota Surabaya? While the purpose of this research is to find out the improvement of student learning outcomes on the subject of flat wake with CTL approach. The location of the research was conducted at MTs Negeri 1 Kota Surabaya, Medokan Semampir Sub-district, East Java. The subjects of this research are the students of class VII B MTs Negeri 1 Kota Surabaya, teacher of grade VII B SD and observer. The study is divided into 2 cycles, each cycle consisting of planning, implementation, observation and reflection. While the indicator of the success of this class action research is achieved if the students have a grade average of at least 75 and mastery learning classes above 75%. In the first cycle students achieve a grade point average of at least 69.87, while the learning mastery is 47.37%. Cycle II reaches the average grade value of 78.16 and the learning completeness is 60.53%. Based on the results of student learning above can be concluded that learning with CTL approach can improve student learning outcomes of class VII B in MTs Negeri 1 Kota Suarabaya on the subject of algebra, so it is recommended that in teaching on the subject of algebra teachers using CTL approach Keywords: Contex Teaching and Learning (CTL), learning outcomes, operation of algebraic forms